Oxidative stress and toxicity produced by arsenic and chromium in broiler chicks and application of vitamin E and bentonite as ameliorating agents - Mashkoor, Javaria; Al-Saeed, Fatimah A.; Guangbin, Zhang; Alsayeqh, Abdullah F.; Gul, Shafia Tehseen; Hussain, Riaz; Ahmad, Latif; Mustafa, Riaz; Farooq, Umar; Khan, Ahrar (Frontiers in Veterinary Science, 2023)
The present study investigated the adverse effects of arsenic and chromium in broilers and ascertained the role of vitamin E and bentonite in alleviating their harmful effects. For this purpose, we experimented on 180 one-day-old broiler chickens. The feed was administered to broiler chicks of groups 2, 6, 7, 8, and 9 chromium @ (270 mg.kg-1 BW). Groups 3, 6, 7, 8, and 9 were administered arsenic @ (50 mg.kg-1 BW). Groups 4, 7, and 9 received vitamin E (150 mg.kg-1 BW), and groups 5, 8, and 9 received bentonite (5%), respectively. Group 1 was kept in control. All the birds treated with chromium and arsenic showed a significant (p < 0.05) decline in erythrocytic parameters on experimental days 21 and 42. Total proteins decreased significantly, while ALT, AST, urea, and creatinine increased significantly (p < 0.05). TAC and catalase decreased significantly (p < 0.05), while TOC and MDA concentrations increased significantly (p < 0.05) in chromium and arsenic-treated groups on experimental days 21 and 42. Pearson correlation analysis revealed a strong positive correlation between TAC and CAT (Pearson correlation value = 0.961; p < 0.001), similarly TOC and MDA positive correlation (Pearson correlation value = 0.920; p < 0.001). However, TAC and CAT showed a negative correlation between TOC and MDA. The intensity of gross and microscopic lesions was more in chromium (270 mg.kg-1) and arsenic (50 mg.kg-1) singly or in combination-treated groups. Thus, broiler birds treated with chromium plus arsenic exhibited higher gross and microscopic lesion intensity than other treated groups. Fatty degeneration, cytoplasmic vacuolation, and expansion of sinusoidal spaces were the main lesions observed in the liver. Kidneys showed renal epithelial cell necrosis, glomerular shrinkage, and cytoplasmic vacuolation. Co-administration of bentonite along with chromium and arsenic resulted in partial amelioration (group 8) compared to groups 7 and 9, administered arsenic+chromium+vitamin E and arsenic+chromium+vitamin E+bentonite, respectively. It was concluded that arsenic and chromium cause damage not only to haemato-biochemical parameters but also lead to oxidation stress in broilers. Vitamin E and bentonite administration can ameliorate toxicity and oxidative stress produced by arsenic and chromium.